Theoretical 3D electron diffraction electrostatic potential maps of proteins modeled with a multipolar pseudoatom data bank. Issue 8 (15th July 2022) - Kulik, Marta; Chodkiewicz, Michał Leszek; Dominiak, Paulina Maria
Abstract : Accurate electrostatic potential maps and electron‐density maps of proteins are calculated based on the transferable aspherical atom model using a pseudoatom data bank and are compared with the experimental data. Abstract : The availability of atomic resolution experimental maps of electrostatic potential from 3D electron diffraction (3D ED) extends the possibility of investigating the electrostatic potential beyond the determination of non‐H‐atom positions. However, accurate tools to calculate this potential for macromolecules, without the use of expensive quantum calculations, are lacking. The University at Buffalo Data Bank (UBDB) gathers atom types that can be used to calculate accurate electrostatic potential maps via structure‐factor calculations. Here, the transferable aspherical atom model (TAAM) is applied with UBDB to investigate theoretically obtained electrostatic potential maps of lysozyme and proteinase K, and compare them with experimental maps from 3D ED. UBDB better reproduces the molecular electrostatic potential of molecules within their entire volume compared with the neutral spherical models used in the popular independent atom model (IAM). Additionally, the theoretical electron‐density maps of the studied proteins are shown and compared with the electrostatic potential maps. The atomic displacement parameters ( B factors) may affect the electrostatic potential maps in a different way than in the case of electron‐density maps. The computational method presented in this study could potentially facilitate the interpretation of the less resolved regions of cryo‐electron microscopy density maps and pave the way for distinguishing between different ions/water molecules in the active sites of macromolecules in high‐resolution structures, which is of interest for drug‐design purposes.